2020
DOI: 10.1177/0954406220936304
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and free vibration analysis of functionally graded sandwich plates and shallow shells by the Ritz method and the R-functions theory

Abstract: The purpose of the paper is to study stability and free vibrations of laminated plates and shallow shells composed of functionally graded materials. The approach proposed incorporates the Ritz method and the R-functions theory. It is assumed that the shell consists of three layers and is loaded in the middle plane. The both cases of uniform as well as non-uniform load are possible. The power-law distribution in terms of volume fractions is applied to get effective material properties for the layers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Jiang et al based on a nonlinearity quantification of the complexity of the trajectories with nonlinearity measures a method for nonlinear system identification method is shown, and in rotor bearing system is applied. Buckling and free of force dynamic analyses of functionally graded sandwich plates and shallow shells using the R-functions in Kurpa and Shmatko 6 with good agreement with the literature results is shown. Mohajed et al 1 with nonlinear dynamic analysis showed the existence of a particular type of modal interactions with a self-adeptness of an attachment to narrow or broadband targeted energy transfers in low or high frequencies.…”
supporting
confidence: 76%
“…Jiang et al based on a nonlinearity quantification of the complexity of the trajectories with nonlinearity measures a method for nonlinear system identification method is shown, and in rotor bearing system is applied. Buckling and free of force dynamic analyses of functionally graded sandwich plates and shallow shells using the R-functions in Kurpa and Shmatko 6 with good agreement with the literature results is shown. Mohajed et al 1 with nonlinear dynamic analysis showed the existence of a particular type of modal interactions with a self-adeptness of an attachment to narrow or broadband targeted energy transfers in low or high frequencies.…”
supporting
confidence: 76%
“…Thus, by putting the value of M ly from equations (7) to (17), one can obtain equation (18), which is the final governing equation of partially cracked orthotropic micro-plate with non-uniform thickness…”
Section: Formulation Of Governing Equation Of a Partially Cracked Orthotropic Plate With Varying Thicknessmentioning
confidence: 99%
“…An analytical investigation of the dynamic behaviour and natural frequencies of laminated nanocomposite plates have done by Khoa and Nguyen 16 Parida and Mohanty 17 used a higher-order shear deformation theory to develop a finite element model for the free vibration analysis of a rotating functionally graded material plate in the thermal environment. Kurpa and Shmatko 18 have proposed the Ritz method and the R-functions theory to study the stability and free vibrations of functionally graded sandwich plates and shallow shells. Civalek 19 has used a discrete singular convolution method to estimate an isotropic and orthotropic plate's natural frequencies with linearly varying thickness.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 It should be noted that wide usage of FG materials were studied more in detail for not only rectangular plates but also for other various mechanical models/components, for example, nano-plates, shells, cylinders, disks, beams, vessels, and spheres. [29][30][31][32][33][34][35][36][37] In this paper, a new method based on the RPT is proposed to investigate the vibration and buckling of rectangular FG plates. This approach does not require a shear correction factor while satisfying shear stress free surface conditions.…”
Section: Introductionmentioning
confidence: 99%